Upaya Peningkatan Literasi kepada Anak-anak di Rumah Belajar Starban Sikkola Rakyat Indonesia - Oktavia Naibaho, Yolanda; Putri, Malida (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2024)
Field Work Practice (PKL) is an activity carried out to provide practical experience directly in the field to students, so that these students are increasingly aware of activities in the field of social welfare professionally and can carry out interventions independently while increasing networks and contributions to the community. Literacy is a fundamental skill that should be developed early in a child's life as it affects their cognitive and social development. Mobilizing literacy in children today is a big challenge and requires a creative and collaborative approach in handling it. This research aims to mobilize the literacy program at Rumah Belajar Starban, Sikkola Rakyat Indonesia, through mini projects in the form of Art Class and Re-Earth. This research uses a qualitative approach with a case study design. Data were collected through observation, interviews and documentation analysis of each mini project activity. The results showed that through the Art Class activities the assisted children were not only involved in reading and writing, but also could think creatively and have the confidence to display their talents. Meanwhile, the Re-Earth program helps provide an understanding of the importance of protecting the environment and hone creative and critical thinking skills in the process of processing plastic waste into works of art. This program has proven to be successful in increasing the interest and motivation of Starban's children towards literacy and also their level of environmental awareness.